Analysis of radiation efficiency effects on UWB MIMO tree-antenna positioning - Muzammil, Jusoh; Mohd Faizal, Jamlos, Dr.; Mohd Fareq, Abd Malek, Dr.; Muhammad Ramlee, Kamarudin; Haslinda, Harun (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/